Socialization and Simulation Method of Basic Living Assistance (BLA) at SMPN 3 Soppeng City - Sapriana; Nurhardianti; Nur Hafizah Binti Ramli; Astry Angrainy Ramadhani; Ummul Hidayah (Althar Cendikia Education, 2025)
Cardiac arrest is a disease that can occur anywhere and at any time. To effectively handle it, knowledge of basic life support (BHD) is required. Basic life support is the initial treatment for victims of cardiac and respiratory arrest. With proper preparedness in providing basic life support, it is hoped that response efforts can be faster and more precise, thereby minimizing the number of victims. The purpose of this activity was to increase students' knowledge and skills in basic life support. The method used was a lecture, namely the delivery of socialization material and BHD support simulation methods. The results obtained were an increase in student knowledge after the socialization and simulation, as evidenced by the percentage of post-test results that increased compared to the percentage of pre-test results that had been conducted. This activity is expected to be carried out periodically to increase the insight of students and the community.